Spray Drying of Food Suspensions: Upgrading Capabilities - Alekseev G.; Egorova O.; Moldovanov D.; Egorov A. (Техника и технология пищевых производств)
Spray drying is currently used to obtain powder products from suspensions. It is considered the most effective type of drying for such media. The complexity of the drying process is associated with thermal destruction of components, which degrades the properties of the product and imposes significant restrictions on temperature condition. The present research features the simulation of transient modes of operation of the solenoids to generate a controlled cavitation effect when applied to a stream of acoustic vibrations using a magnetostrictive generator of ultrasound. The authors propose a new design of spray nozzle for drying suspensions with counter-connected solenoids. Such solenoids can cause deformation of the main suspension supply line. The intensity of the cavitation processes depends on the dynamics of the solenoid actuation. The paper introduces a mathematical modeling of transient modes of operation for ultrasonic frequency generator solenoids that create a controlled cavitation effect when applied to the jet of acoustic oscillations of this frequency. When modeling the process of operation of solenoids, the main criterion for changing the intensity of cavitation is the average rate of change in the volume of the cavity at the stage of its collapse, related to one cycle of oscillations for a spherical cavity. An increase in the static pressure of the liquid led to a shift in the phase of the collapse of the cavity. As a result of the chosen mathematical model, a numerical experiment with modeling in the MathCAD program was carried out. It revealed some graphical dependences of the change in U(t), L(t), and R(t). The obtained data allow one to predict the ballast induction and active load (R, L) for the control of transients in the solenoid of the ultrasonic generator. These dependences make it possible to choose more effective parameters for drying suspensions, which is especially important for heat- sensitive components.